Severe COVID-19 pneumonia in a pregnant lady with diabetes mellitus and bronchial asthma: a case report from a semi-urban primary care center in Bangladesh (BIRDEM Medical Journal, 2023)
Pregnant women are more susceptible to complications from respiratory disease due to physiological changes in pregnancy. Coronavirus disease 2019 (COVID-19) like its ancestors, severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle-East respiratory syndrome coronavirus (MERS-CoV), may be associated with more severe disease course in pregnancy and possible adverse outcome to mother and the newborn baby. Here, we present a case of a pregnant lady with severe COVID-19 with oligohydraminos with less fetal movement managed in a resource poor primary care setup.BIRDEM Med J 2023; 13(2): 107-110